Roaming the Seas—Assessing Marine Invertebrate Biodiversity Along Salinity Gradients With Zooplankton and eDNA Metabarcoding - Alica Ohnesorge; Uwe John; Lucie Kuczynski; Stefan Neuhaus; Kingsly Chuo Beng; Bernd Krock; Silke Laakmann (Environmental DNA, 2024)
ABSTRACT Marine metazoan biodiversity is accretively being explored through environmental DNA (eDNA) metabarcoding of seawater. However, knowledge gaps in the use of eDNA to study changes in diversity resulting from changing abiotic conditions still do exist. In order to address these gaps, we analyzed patterns of marine invertebrate biodiversity based on eDNA from water and sediment samples along a decreasing salinity gradient from the North Sea toward the Baltic Sea. eDNA was collected from surface (SW) and bottom (BW) water, and from the uppermost sediment layer (SE). To supplement the eDNA approach, we conducted parallel zooplankton (ZP) metabarcoding and morphological identification. DNA was extracted from eDNA and ZP samples, amplified using two universal primers that target of the mitochondrial cytochrome c oxidase subunit 1 (COI) and the nuclear ribosomal 18S rRNA genes, and paired‐end sequenced on Illumina Miseq. Metabarcoding detected 279 metazoan species (from 16 phyla) of which > 87% are known from the study area or adjacent regions. Communities identified in SW eDNA were a subset of communities identified in ZP metabarcoding. BW eDNA had additional benthic (mainly bivalve) species. Communities identified in SE eDNA were distinct from those in water eDNA and ZP metabarcoding, and mainly represented by in‐ and meiofauna. Out of all approaches, only ZP metabarcoding uncovered the expected decrease in species richness toward brackish conditions. Neither salinity nor spatial distance had a significant effect on species composition. All approaches revealed regional differences of which SE eDNA was least informative. The detection of holoplanktonic species from SE eDNA provided evidence for sinking of eDNA particles, dead organisms or the presence of resting eggs. Our study confirms the value of metabarcoding to identify the North Sea and Baltic Sea invertebrates and underscores the importance of combining multiple approaches to understand invertebrate biodiversity and its change in the marine realm.